Variables asociadas a resiliencia en personas con diabetes tipo 2 atendidos en la estrategia no transmisibles Hospital Regional de Loreto Iquitos 2024 - Pérez Valderrama, Mónica Milagros (2025)
The research project aims to determine the variables associated with resilience in people treated under the non-communicable strategy of the Loreto Regional Hospital in Iquitos 2024.The type of research was quantitative, with a non-experimental, descriptive, correlational and cross-sectional design. The sample consisted of 86 people with type 2 diabetes. The technique used was the interview, the survey and the instruments were the Data Sheet for people with type 2 diabetes and the Resilience Scale for people with type 2 diabetes by Wagnild and Young. According to the results, 47.7% were between 35 and 49 years old, 54.7% were female, 45.3% had a university degree, 45.3% were independent, 44.2% had less than 1 year of illness, 40.7% suffered from cancer as a comorbidity. Regarding resilience, 45.3% had a high resilience, 45.3% (39) had moderate resilience and the remaining 9.3% had low resilience. In conclusion, it was shown that there is an association with age (p = 0.001), sex (p = 0.003), educational level (p = 0.001), occupation (p = 0.000), time of illness (p = 0.001) and comorbidity (p = 0.004).